2021
DOI: 10.3390/molecules26185683
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Factors and Cytokines of Dental Pulp Mesenchymal Stem Cell Secretome May Potentially Aid in Oral Cancer Proliferation

Abstract: Background: Growth factors and cytokines responsible for the regenerative potential of the dental pulp mesenchymal stem cell secretome (DPMSC-S) are implicated in oral carcinogenesis. The impact and effects of these secretory factors on cancer cells must be understood in order to ensure their safe application in cancer patients. Objective: We aimed to quantify the growth factors and cytokines in DPMSC-S and assess their effect on oral cancer cell proliferation. Materials and methods: DPMSCs were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Dominant therapeutic effects of DPSCs depend on the presence of growth factors, cytokines and osteoinductive agents. Possibly, there are several uninvestigated approaches through the modulation of growth factors and cytokine productions 15 . For example, researchers' DPSC treatments with cobalt-chromium and hypoxic induction have led to growth factor alterations in the cells, enhancing their regenerative potentials 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Dominant therapeutic effects of DPSCs depend on the presence of growth factors, cytokines and osteoinductive agents. Possibly, there are several uninvestigated approaches through the modulation of growth factors and cytokine productions 15 . For example, researchers' DPSC treatments with cobalt-chromium and hypoxic induction have led to growth factor alterations in the cells, enhancing their regenerative potentials 14 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is an inflammatory cytokine which takes part in the maintenance of various cellular signaling processes (118). TNF-a is one of the most abundant pro-inflammatory cytokines followed by CXCL-8 in the oral MSC secretome, which could potentially mediate tumor development (119).…”
Section: Tumor Necrosis Factor Alphamentioning
confidence: 99%
“…TNF-α is an inflammatory cytokine which takes part in the maintenance of various cellular signaling processes ( 118 ). TNF-α is one of the most abundant pro-inflammatory cytokines followed by CXCL-8 in the oral MSC secretome, which could potentially mediate tumor development ( 119 ). Tumor associated macrophages (TAMs) play a vital role in the production of TNF-α which can be associated with increased stemness in OC ( 120 ).…”
Section: Extrinsic Factors Governing Oscc Stemnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Ki-67 assays, Raj et al (2021b) indicated the dual effect of MSCs on tumors. DPSCs-CM inhibited the proliferation of TSCC cells AW13516 at 50% and 100% concentrations and promoted the proliferation at a 20% concentration.…”
Section: Effects Of Mesenchymal Stem Cells On Oral Cancermentioning
confidence: 99%